PROGRAM KEMITRAAN MASYARAKAT PADA PENGELOLAAN GREEN HOUSE SMART FARMING DI DUKUH TAMBAK, NGESTIHARJO, BANTUL - Santoso, Banu; Sari, Marti Widya; Tri Hartanti, Ninik; Prasetya, Dian (Jurnal Berdaya Mandiri, 2023)
This community service was carried out in the Tambak Hamlet, Ngestiharjo Village, Kasihan, Bantul, Yogyakarta. Tambak Hamlet is a hamlet located in the Ngestiharjo Village, Bantul, which is on the outskirts of Yogyakarta. Therefore, the population in this area is quite dense, so that agricultural land becomes increasingly limited. Narrow land still exists in this area, which can be used for farming or planting horticultural crops. However, nowadays the weather is getting more and more erratic, so the time for planting is becoming more difficult. In Tambak Hamlet there is already an IoT-based green house for smart farming for horticultural crops, but it has not been managed, because it is still in the development stage. Based on this, the service team is trying to make a suggestion regarding the management of the green house, so that the results can be maximized and able to increase the economic value for the community. This service aims to develop agricultural digitalization through the Smart Farming Model, using Internet of Things (IoT) technology, to assist in crop monitoring, so that the growth and yield of horticultural crops is optimal. The purpose of this service is in line with the 3rd and 5th Main Performance Indicators (IKU) of Higher Education. The 3rd IKU, namely lecturers who carry out activities outside the campus, in this case the lecturer performs community service which is carried out in the Tambak Hamlet. The 5th IKU is the work of lecturers used by the community, namely in the form of ideas and thoughts in the development of smart farming. The expected outputs from this community service activity are services in the form of training and assistance for the management of green house smart farming, and publication in the form of scientific articles that will be published in national journals. Keywords: smart farming, green house, community service, digitalization, agriculture